How to use low-molecular-weight heparin to treat neonatal thrombosis in clinical practice. Issue 8 (December 2021) - Ting, James; Yeung, Klement; Paes, Bosco; Chan, Anthony K.C.; Petropoulos, Jo-Anne; Banfield, Laura; Bhatt, Mihir D.
Abstract : N/A: Among children, neonates have the highest incidence of thrombosis due to risk factors such as catheter instrumentation, an evolving coagulation system and congenital heart disease. Low-molecular-weight heparins (LMWHs) are the most commonly used anticoagulants in neonates. Published guidelines delineate dosing and monitoring protocols for LMWH therapy in newborns. However, challenging clinical situations frequently present that warrant healthcare providers to think critically beyond the range of guidelines, and judiciously resolve specific problems. This review describes the use of LMWH in the neonatal population, including practical aspects such as route and site of administration, preparation from concentrated formulations and methods to minimize pain of subcutaneous injection. It is followed by a discussion on dosing, monitoring and outcomes of LMWH therapy in neonates. The risk of recurrence of thrombosis in neonates after LMWH therapy is approximately 3% based on a pooled analysis of studies reporting this outcome over the last 24 years. The article concludes with an overview of the side-effects of LMWH, including the risk of bleeding which is around 4% based on pooled analyses of more than 30 studies.